Time trend by region of suicides and suicidal thoughts among Greenland Inuit - Bjerregaard, Peter; Larsen, Christina Viskum Lytken (International Journal of Circumpolar Health, 2015)
BACKGROUND: Suicides remain a major public health problem in Greenland. Their increase coincides with the modernization since 1950. Serious suicidal thoughts are reported by a significant proportion of participants in countrywide surveys. OBJECTIVE: To analyze the time trend by region of suicides and suicidal thoughts among the Inuit in Greenland. DESIGN: Data included the Greenland registry of causes of death for 1970-2011 and 2 cross-sectional health surveys carried out in 1993-1994 and 2005-2010 with 1,580 and 3,102 Inuit participants, respectively. RESULTS: Suicide rates were higher among men than women while the prevalence of suicidal thoughts was higher among women. Suicide rates for men and women together increased from 1960 to 1980 and have remained around 100 per 100,000 person-years since then. The regional pattern of time trend for suicide rates varied with an early peak in the capital, a continued increase to very high rates in remote East and North Greenland and a slow increase in villages relative to towns on the West Coast. Suicidal thoughts followed the regional pattern for completed suicides. Especially for women there was a noticeable increasing trend in the villages. The relative risk for suicide was highest among those who reported suicidal thoughts, but most suicides happened outside this high-risk group. CONCLUSION: Suicide rates and the prevalence of suicidal thoughts remain high in Greenland but different regional trends point towards an increased marginalization between towns on the central West Coast, villages and East and North Greenland. Different temporal patterns call for different regional strategies of prevention.